Prevalence and Correlates of Diurnal Mood Variation in Chinese Adolescents with Major Depressive Disorder and Anxiety Symptoms: A Cross-Sectional Study - Duan J; Zhang Y; Tao J; Fan X (Neuropsychiatric Disease and Treatment)
Jiawen Duan, Yijing Zhang, Jingyi Tao, Xiwang Fan Clinical Research Center for Mental Disorders, Shanghai Pudong New Area Mental Health Center, Tongji University School of Medicine, Shanghai, People’s Republic of ChinaCorrespondence: Xiwang Fan, Clinical Research Center for Mental Disorders, Shanghai Pudong New Area Mental Health Center, Tongji University School of Medicine, 165 Sanlin Road, Pudong New Area, Shanghai, 200124, People’s Republic of China, Tel/Fax +86 021 68306699, Email fanxiwang2020@163.comPurpose: Diurnal mood variation is one of the prominent symptoms in depression. However, little is known about this phenomenon. This study examined diurnal variation in adolescents with comorbid depression and anxiety symptoms, and assessed the incidence, correlates, and related factors.Patients and Methods: The study comprised a sample of 557 outpatients who were adolescents suffering from anxiety and depression. Symptom severity was assessed using the Zung Self-Rating Depression Scale, Anxiety Scale, and 24-item Hamilton Rating Scale for Depression.Results: Majority of the participants (69.83%) reported diurnal mood variation throughout the day. Higher score on the Zung Self-Rating Depression Scale, specifically somatic, cognitive impairment, retardation, sleep disturbance, and feelings of despair, were noted in individuals with diurnal variation compared to those without. Additionally, there was a significant correlation between feelings of despair and diurnal mood variation, which was able to predict diurnal variation in adolescent aged 10 to 13 years or those whose depressive symptoms were mild.Conclusion: Diurnal mood variation is common in adolescents with major depressive disorder and anxiety. The pattern is associated with more severe depressive symptoms. Feelings of despair are a potential associated factor for diurnal changes in mood, although the discriminatory capacity of this variable is limited. Keywords: diurnal variation, major depressive disorder, anxiety symptoms, adolescent